Oral status and affecting factors in Iranian ICU patients: a cross-sectional study - Mostafa Arkia; Jahangir Rezaei; Nader Salari; Siavash Vaziri; Alireza Abdi (BMC Oral Health, 2023)
Abstract Background Oral care is crucial in intensive care units (ICUs). Meanwhile, this action is not well-performed, therefore, mouth cavity-associated disorders cause serious outcomes, e.g. ventilator-dependent pneumonia. Considering a lack of studies in Iran on this subject, this study aimed to determine the oral status and affected factors in ICU patients in Iran. Methods In a cross-sectional study in 2019, we assessed the oral status of 138 patients admitted to the ICUs in the Kermanshah and Ilam provinces by census method. The tools were a demographic and clinical characteristics checklist, and Beck's oral status assessment scale (BOAS). The researcher investigated the condition of the patient's mouth, and their records. Data were analyzed using descriptive and inferential statistics. Results In this study, the prevalence of moderate and severe disorders of the lips, gums and oral mucosa, tongue, teeth, and saliva were 14.4, 26.1, 16.6, 49.3, and 34.8 percent, respectively. Six percent of patients had a normal oral condition. Oral status had a significant relationship with education level, age, marital status, brushing teeth, NG tube, and consciousness level. Conclusion Compared to other studies, the prevalence of oral cavity disorders in ICU patients of the Ilam and Kermanshah provinces was high. It mandates paying crucial attention to nurses' continued education, using standard guidelines, and applying new facilities. Moreover, it is mandated for periodical visits of patients by a dentist in ICUs.